Синфітоіндикаційна оцінка едафотопів лісових екосистем за даними моніторингу лісів лісостепової частини України - Bondaruk, M.A.; Tselischev, O. G. (Ukrainian Research Institute of Forestry and Forest Melioration named after G. M. Vysotsky (URIFFM), 2021)
Introduction The impact of climate change on forests in Ukraine differs significantly depending on the geomorphology and relief, physical, chemical, and hydrological characteristics of soils, forest types, and differences in their vegetation. Therefore, the forest monitoring system should also include the monitoring of forest edaphic regimes. The aim of the study was to make synphytoindication assessment of edaphotopes of forest ecosystems in the Forest-Steppe forestry region of Ukraine for the implementation of regional (zonal) monitoring of edaphic regimes of forest ecosystem ecotopes. Materials and Methods Forest vegetation at 64 first-level forest monitoring plots within the Forest-Steppe forestry region of Ukraine (49 forest types in 15 types of forest site conditions are represented: А1-А3, В1-В3, С1-С4, D1-D5). Characterization of forestlands was carried out using the guidelines for forest monitoring to determine the location according to forest zoning, forest types, and types of forest stands. The geobotanical description included species of trees, shrubs, and herbaceous plants which were estimated on their abundance-coverage (%) according to the combined scale of G. M. Vysotsky and D. V. Vorobyov. The phytoindication method for determining factors according to the unified scales of ecological amplitudes for flora species in Ukraine (Didukh, 2011) was used for synphytoindication assessment of edaphotopes of forest ecosystems. To analyse trends in soil regimes changes and their differentiation at the level of forest types, the minimum (хmin), average () and maximum (хmax) values of edaphic regimes according to the types of forest conditions, forest communities (coniferous, mixed, deciduous) and in general for forestry region were calculated. Results Edaphic regimes of forest soils in Forest-Steppe region vary within the ranges: hydrological (Wnp = 90–235 mm), moisture variability (? = 0,17–0,33), acidic (pH = 4.4-8.0), mineralization (Sl = 0,0075%, НСО3?, SO42-, Cl? absent, available H+, Al3+, Fe2+ up to 0.02%, НСО3? = 0,03-0,05% of soil and traces of SO42- and Cl?) , carbonate content (CaO, MgO = 0.5-2.0%) and soluble forms of nitrogen Nt = 0.05-0.5%). Trends in the dynamics of average values of edaphic regimes indicators of forest ecotopes within Forest-steppe forestry region according to change of forest conditions are defined: soil moisture increasing is observed according to hydrologic series; the lowest values of soil moisture variability are in wet and moist ecotopes, the largest ones in dry ecotopes; the lowest values of salt regime of soils are in poor and relatively poor sites, the highest ones in dry and moist relatively rich and rich site conditions; increase in the content of mineral nitrogen in soils is according to trophotope series: poor sites – relatively poor sites – relatively rich sites – rich sites; increase in alkalinity, carbonate content, and deterioration of forest soil aeration level is also according to trophotope series only within the same hydrological conditions, and within one trophotope the decrease in pH, carbonate content and deterioration of aeration level against the background of forest soil moisture increasing are observed. Conclusions Forest monitoring investigations must include monitoring of edaphic regimes of ecotopes in forest ecosystems along with climatic ones (direct measurements and synphytoindication methods). Comparison of the obtained scores in different time periods (once every five years) in each region of Ukraine will allow assessing the intensity, depth, direction (trend), spatial distribution, and features of changes in edaphic regimes at the regional and national levels due to global climate change on forest ecosystems in Ukraine.